2012
DOI: 10.1177/875687051203100203
|View full text |Cite
|
Sign up to set email alerts
|

Parent Training for Families who have Children with Autism: A Review of the Literature

Abstract: The purpose of this review was to examine the literature on parent training for parents of children with autism. Families with a child diagnosed with autism often face a discrepancy between their need for services and the availability of services either because they live in geographically distant areas or because they are on a long wait list for services. Researchers have found that parents, if trained, can serve as a facilitator of positive change for their child. There is a plethora of home- and facility-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 62 publications
(112 reference statements)
0
28
0
1
Order By: Relevance
“…Although multiple reviews have found that parents are capable of learning techniques and facilitating programming (Matson et al, 1996; McConachie & Diggle, 2007; Suppo & Floyd, 2012), most of the literature reviews to date have focused on programs for families of younger children, and no syntheses have evaluated the effects of PT for school-aged children with ASD. This is unfortunate because older children with ASD continue to experience difficulties, and PT may remain necessary to support families and promote positive outcomes as children age.…”
Section: Effects Of Pt Interventionsmentioning
confidence: 99%
“…Although multiple reviews have found that parents are capable of learning techniques and facilitating programming (Matson et al, 1996; McConachie & Diggle, 2007; Suppo & Floyd, 2012), most of the literature reviews to date have focused on programs for families of younger children, and no syntheses have evaluated the effects of PT for school-aged children with ASD. This is unfortunate because older children with ASD continue to experience difficulties, and PT may remain necessary to support families and promote positive outcomes as children age.…”
Section: Effects Of Pt Interventionsmentioning
confidence: 99%
“…Safety information specific to autism should be included when a child is diagnosed and would enable parents to be proactive about safety. The various education programs found for parents who have children with autism are not standardized and it is not known to what extent safety concerns are addressed (Beaudoin et al, ; Meadan, Meyer, Snodgrass, & Halle, ; Steiner, Koegel, Koegel, & Ence, ; Suppo & Floyd, ; Tonge, Brereton, Kiomall, Mackinnon, & Rinehart, ). To our knowledge, current autism‐specific safety recommendations to educate these parents at well‐child visits do not exist.…”
Section: Discussionmentioning
confidence: 99%
“…Research that discusses education for parents who have autistic children exists (Bearss, Burrell, Stewart, & Scahill, ; Bearss, Johnson, Handen, Smith, & Scahill, ; Beaudoin, Sebire, & Couture, ; Machalicek et al, ; Suppo & Floyd, ; Suppo & Mayton, ; Vismara, McCormick, Young, Nadhan, & Monlux, ). These studies focused on different methods for educating parents and preventing challenging but none of the studies indicated if safety concerns that are common with autism were addressed.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, the number of children with ASD is increasing, but services are only available in major cities. In addition, due to the limited resources, waiting times for appointments or family-centered approach sessions can take 8-12 weeks [17]. Moreover, several aspects, including the costs of travel and the service itself as well as the need to manage receipt of support for their child while maintaining jobs and fulfilling other responsibilities, lead to a significant strain on families living in rural areas of KSA [2,17,18].…”
Section: Barriers and Challenges In Adopting Saudi Telehealth Servicementioning
confidence: 99%
“…For such families, telehealth could address many such issues and provide additional support to existing services. Telehealth services could be used as a tool for teaching strategies to improve the outcomes of children with ASD and their families [17,19]. However, the cultural context, beliefs, educational levels, and socioeconomic status of the KSA population need to be considered when selecting appropriate methods of intervention [18].…”
Section: Barriers and Challenges In Adopting Saudi Telehealth Servicementioning
confidence: 99%